Application of Bio Fertilizer and Biogas Sludge to Curly Red Chili (Capsicum annuum L.) at Wukirsari Village, Cangkringan, Sleman - Dwi Umi Siswanti; Utaminingsih Utaminingsih; Melinda Fajar Lestari; Hamdian Hamdian (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Curly red chili (Capsicum sp.) is an important agricultural commodity in Indonesia. The pattern of conventional cultivation using inorganic fertilizers has caused high production costs. While the level of spiciness of chili determined by capsaicin levels is strongly influenced by nutrients in the growing media. Bio fertilizer and sludge biogas biogas which is one of the organic fertilizers proved to be able to increase the growth and productivity of rice plants. This study aimed to analyze growth parameters, chlorophyll content and measure capsaicin levels in curly red chili. Which given bio fertilizer and biogas sludge biogas in various dosage and determine the optimum dose of the fertilizer. The study was conducted at an agricultural demonstration plot in Wukirsari Village, Cangkringan, Sleman. The study design used RCBD (Randomized Complete Block Design), the data were analyzed by ANOVA (Analysis of Variance followed by Duncan's multiple distance test (DMRT) at the 95% confidence level. The highest growth parameters was obtained on curly red chili plants which were given sludge biogas 36 mL + bio fertilizer 10 L / ha. Thus, it can be concluded that the most appropriate dose of curly red chili is 36 mL sludge biogas +  bio fertilizer 10 L/ha.Keywords: Bio-fertilizer; biogas; chili; growth;sludge; Wukirsari.